The world according to Garp [videorecording (DVD)] - Williams, Robin, 1951-2014; Hurt, Mary Beth; Close, Glenn, 1947-; Irving, John, 1942- (Warner Bros. Entertainment, 2014)
T. S. Garp is a sweet-natured writer whose life is a weird minefield of violence, adultery, fatherhood, feminism, and eerie coincidences.